2015
DOI: 10.1039/c5tb00053j
|View full text |Cite
|
Sign up to set email alerts
|

Poly[3,4-ethylene dioxythiophene (EDOT)-co-1,3,5-tri[2-(3,4-ethylene dioxythienyl)]-benzene (EPh)] copolymers (PEDOT-co-EPh): optical, electrochemical and mechanical properties

Abstract: PEDOT-co-EPh copolymers with systematic variations in composition were prepared by electrochemical polymerization from mixed monomer solutions in acetonitrile. The EPh monomer is a trifunctional crosslinking agent with three EDOTs around a central benzene ring. With increasing EPh content, the color of the copolymers changed from blue to yellow to red due to decreased absorption in the near infrared (IR) spectrum and increased absorption in the visible spectrum. The surface morphology changed from rough and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 54 publications
(98 reference statements)
1
47
0
Order By: Relevance
“…Hundreds of nanometers of blue shifts in absorption maxima were observed with EPh as crosslinker, leading to dramatic changes in color. 12 The blue shift of absorption was resulted from the decreased conjugated chain length which could potentially lead to an eventual loss in charge transport efficiency, usually larger blue shift could result in more loss of conductivity. However, in this system, much smaller shifts in absorption were observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hundreds of nanometers of blue shifts in absorption maxima were observed with EPh as crosslinker, leading to dramatic changes in color. 12 The blue shift of absorption was resulted from the decreased conjugated chain length which could potentially lead to an eventual loss in charge transport efficiency, usually larger blue shift could result in more loss of conductivity. However, in this system, much smaller shifts in absorption were observed.…”
Section: Resultsmentioning
confidence: 99%
“…These shifted oxidation peaks indicated that the crosslinker decreased the conjugation length of PEDOT. 12, 35, 37 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conducting polymer coatings are known to dramatically decrease electrode impedance and increase charge injection limit [18, 106], and have been used to enable recording from ultrasmall electrode sites [47, 107]. New advances in conducting polymers may be found in novel dopants [61, 89], drug delivery [89], and novel monomers and crosslinkers for ease of functionalization or improved stability [108111]. These novel polymer coatings may allow for further decreased size of both recording and stimulating electrodes for central and peripheral nervous system applications.…”
Section: Strategiesmentioning
confidence: 99%